PERSENTASE KARKAS AYAM KAMPUNG SUPER YANG DIBERI TEPUNG USUS AYAM SEBAGAI SUBSTITUSI TEPUNG IKAN DALAM RANSUM - Mohamad Indra Rupu; Syahruddin Syahruddin; Srisukmawati Zainudin (Jambura Journal of Animal Science, 2022)
This study aimed to determine the weight and carcass percentage of super free-range chicken given broiler chicken intestine flour as substitution of fish meal in the fed ration. The study used experimental methods arranged in a Completely Randomized Design (CRD) consisting of five treatments and four replications in order to obtain 20 experimental units. The experimental used were one hundred super free-range chickens which were day old chick. The chickens were placed in 20 colony cages, each of which was filled with 5 birds. The treatment of fed ration consisted of P0 (Fed ration with 10% fish meal, without chicken intestine flour), P1 (7.5% fish meal + 2.5% chicken intestine flour), P2 (5.0% fish meal + 5.0% chicken intestine flour), P3 (2.5% fish meal + 7.5% chicken intestine flour) and P4 (Fed ration without fish meal + 10% chicken intestine flour). After 8 week old (56 days) the chickens were slaughtered and the carcass parts separated. The variables observed were live body weight, carcass weight, carcass percentage of the thigh, chest, back and wings. The results showed that the treatment had no significant effect (P0.05) on live body weight, carcass percentage and carcass percentage of the thigh, breast, back and wing of super free-range chickens. It was concluded that broiler chicken intestine flour could be used up to 10% level as a substitute for fish meal in the ration and did not reduce body weight and carcass percentage of super free-range chickens.